Light‐Emitting Diodes: Highly Efficient Orange and Red Phosphorescent Organic Light‐Emitting Diodes with Low Roll‐Off of Efficiency using a Novel Thermally Activated Delayed Fluorescence Material as Host (Adv. Mater. 27/2015). (July 2015) - Wang, Hui; Meng, Lingqiang; Shen, Xingxing; Wei, Xiaofang; Zheng, Xiuli; Lv, Xiaopeng; Yi, Yuanping; Wang, Ying; Wang, Pengfei
<x xml:space="preserve">Abstract</x> A novel host material, MTXSFCz, with the thermally actived delayed fluorescent property is reported by Y. Wang, P. Wang, and co‐workers on page 4041 for the construction of red and orange phosphorescent organic light‐emitting diodes (PHOLEDs) with low efficiency roll‐off. The efficient reverse intersystem crossing of the MTXSFCz host from triplet to singlet facilitates the reduction of the triplet density on the host and then diminished triplet–triplet annihilation and triplet–photon annihilation, leading to the low efficiency roll‐off of the PHOLEDs.